Reinstatement and phylogenetic allocation of the palm rust genus Cerradoa in the Pucciniaceae, and establishment of Pseudocerradoa, gen. nov. - Ebinghaus, Malte (2022)
The genus Cerradoa (type species Cerradoa palmaea) was established in 1978 by Hennen and Ono and named after the Brazilian Cerrado biome. The holotype collected in Planaltina, Federal District, Brazil, belonged to the first rust fungus reported on palms (Arecaceae). For decades, the status of Cerradoa as a distinct genus has been regarded as doubtful, representing a synonym of Edythea (Uropyxidaceae) starting with the second edition of the Illustrated Genera of Rust Fungi in 1983. Our molecular phylogenetic analyses, as well as our morphological investigations, allowed us to reject this synonymy, leading to the reinstatement of Cerradoa within the Pucciniaceae. Cerradoa, together with morphologically similar genera such as the newly established Pseudocerradoa with two species (Ps. paullula and Ps. rhaphidophorae) infecting araceous hosts, the fern rust Desmella, and also P. engleriana, could not be assigned to any of the seven identified major lineages within the Pucciniaceae. Edythea, instead of being maintained as a member of the Uropyxidaceae, was herein placed in Pucciniaceae, shown hylogenetically in close relationship to Cumminsiella mirabilissima, both infecting the Berberidaceae. Additionally, our extensive phylogenetic analyses add guidance for future taxonomic revisions in the highly polyphyletic genus Puccinia and other established taxa within the family Pucciniaceae.